THE ROLE OF FORENSIC ACCOUNTING IN DETECTING AND INVESTIGATING CASES OF CORPORATE FINANCIAL FRAUD - Hermiyetti Hermiyetti (INJOSEDU: International Journal of Social and Education, 2025)
This study aims to explore the important role played by forensic accounting in detecting and investigating financial fraud. The research method used is literature. The results showed that forensic accounting is an effective instrument in identifying and exposing financial fraud. By using data analysis tools and specialized investigative techniques, forensic accountants can detect unusual patterns that may signal fraud. Their skills and experience in evidence assessment and preparation of investigative reports provide significant support in legal proceedings. The findings also confirm that forensic accountants play a vital role as expert witnesses in court, as well as in making recommendations for improvements to internal control systems to reduce the risk of future fraud.